Uma análise do modelo SIRS e o estudo de suas bifurcações - Jéssica Duarte Silva Guimarães (2022)
This dissertation is about the analysis of a study on an epidemiological model with general non-linear incidence rate, which we have the SIR model (Susceptible-Infected- Recovered) with a generalization. The study with the objective of establishing conditions for the quantity and stability of the balance points will be done, and this will lead us to the behavior of some bifurcations even with the disease controlled.